Personal support and expressions of care for pregnant women in Soweto, South Africa - Langelihle Mlotshwa; Lenore Manderson; Sonja Merten (Taylor & Francis Group, 2017)
Background: Pregnancy is life changing, making great demands on women to adapt physically, psychologically, and socially. Social relationships and the support that flow from these provide a critical role in managing health problems in pregnancy. Isolation and lack of care, in contrast, may lead women to experience increased distress during this time. Objective: This study aimed to explore South African women's perception and experience of care and support in pregnancy. Methods: A life history approach was employed to explore women's experiences of pregnancy and sexual behaviour, with each participant encouraged to narrate important life events from her own perspective. We drew on narrative interviews with 15 pregnant women, conducted between July and October 2015, in which we explored questions regarding pregnancy planning and the provision and receipt of care. A thematic approach was employed to code and analyse the data. Results: Themes that emerged from the interviews showed that participants gained a sense of stability in their lives when they had support in their pregnancy, especially when dealing with challenging situations. This support came variously from family, friends, and social networks. Overall, those participants who mentioned the most support, and its diversity across different groups, reported a better experience of pregnancy. Conclusions: Women emphasised the importance of social and emotional support in pregnancy. Understanding women's experiences can assist in making pregnancy less overwhelming, and can add to a woman's ability to deal with different challenges before and after the arrival of the new baby.